Dancing together at arm's length? – The interaction of central banks with governments in the G7 - Cristina Bodea; Stefan Huemer (European Central Bank (ECB), 2010)
Central bank independence is a common feature in advanced economies. Delegation of monetary policy to an independent central bank with a clear mandate for price stability has proven to be successful in keeping a check on inflation and providing a trusted currency. However, it is also a fact that central banks in most countries have regular contacts with the government and cooperate with them on a number of issues. This paper looks into the various forms of cooperation between central banks and governments in the G7. The focus is on those central banks that exercise a monetary policy decision-making function, i.e. the ECB and the central banks of the four G7 countries outside the euro area (the US, UK, Japan and Canada). The paper first reviews the objectives of and arrangements for central bank/government cooperation in the US, UK, Japan and Canada in areas such as monetary policy and its interlink with economic policy; foreign exchange operations and foreign reserve management; international cooperation; payment systems/securities learing and settlement systems; upervision, regulation and financial stability; banknotes and coins; collection of statistics; and the role of fiscal agent for the government. In parallel the paper looks into the objectives of and arrangements for cooperation between the ECB and relevant European counterparts, reflecting the specific European institutional environment characterised by the absence of a `European government'. Following a comprehensive stocktaking of practices, the paper embarks on a comparison of existing arrangements, pointing to the similarities and differences among the five surveyed central banks. The Appendix provides a more in-depth description of central bank/government cooperation per country and topic; it presents the detailed factual background on which the paper builds, serving as a reference for the reader interested in more detail.
Keywords: D83; C62; E30; 330; central bank governance; central bank tasks; Central bank-government cooperation; G7; Zentralbankunabhängigkeit; Geldpolitik; Kooperation; Zentralbank; Regierung; Eurozone; Großbritannien; Japan; Kanada; USA